Pertanggungjawaban Pidana terhadap Pelaku Eksploitasi Anak melalui Pemanfaatan Anak sebagai Pengemis Jalanan dalam Perspektif Hukum Pidana Indonesia. - Daniel Sianturi; Radhin Naufal Faris; Taun Taun (Journal Of Human And Education (JAHE), 2026)
Child exploitation through the use of children as street beggars remains a problem despite the prohibition of economic exploitation of children under Indonesian criminal law. This research aims to analyze the regulation and legal construction of child exploitation through the use of children as street beggars and the criminal liability of perpetrators. This research employs a normative juridical method using statutory, conceptual, and case approaches. Legal materials are analyzed descriptively, analytically, and argumentatively by examining the applicable legal provisions in relation to the alleged exploitation of three children in Pangkalan Kerinci, Pelalawan Regency, Riau, in 2026. The results show that the use of children as street beggars may constitute economic exploitation when it is proven that a person places, permits, commits, orders, or participates in exploiting a child for economic gain. Criminal liability may be imposed on perpetrators who fulfill the elements of the offense, possess culpability and capacity to be held responsible, and are not subject to grounds excluding culpability.